Genetic diversity analysis of Sangamneri goat - NATH, SAPNA; KURALKAR, S V; KHAN, WAQAR; KHARKAR, KRANTI; KURALKAR, PRAJAKTA (The Indian Journal of Animal Sciences, 2014)
Sangamneri, one of the important dual-purpose goat breed of Maharashtra existing in the villages of Nasik, Ahmednagar and Pune district was investigated genetically utilizing 25 microsatellite markers. The observed number of alleles varied from 8 (ILSTS 002, ILSTS 065) to 32 (ILSTS 008) with an overall mean of 16.800±1.109. The effective number of alleles ranged from 3.663 (ILSTS 065) to 19.208 (ILSTS 008) with a mean of 10.751±0.808. The observed heterozygosity ranged from 0.000 (ILSTS 002) to 1.000 (ILSTS 033, ILSTS 058) with an average of 0.732±0.059, whereas the expected heterozygosity varied from 0.735 (ILSTS 065) to 0.958 (ILSTS 008) with an overall mean of 0.900±0.011. All of the studied loci showed the polymorphic information content (PIC) value greater than 0.5 with an average value of 0.881±0.012, these high values of PIC indicated higher polymorphism in the breed. The values Shannon’s information index ranged from 1.648 (ILSTS065) to 3.204 (ILSTS008) with an average of 2.487±0.076. Heterozygosity deficiency (positive Fis value) was observed in 18 out of 25 studied loci indicating departures from random mating. The mode shift analysis generated L–shaped distribution curve indicating that the population has not undergone any bottleneck in the recent past.